Resource-Based View, Dynamic Capabilities, and Entrepreneurial Orientation: Their Impact on MSME Performance and Sustainable Competitive Advantage of MSMEs in Bali - Ni Made Widnyani; Arif Agus Riyanto; Elok Rosyidah; Ni Made Ary Lisnawati; Kadek Riyan Putra Richadinata; Cokorda Istri Dharmayanti (Universitas Pendidikan Nasional, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Bali play a crucial role in employment absorption, driving the tourism sector, and strengthening the regional economy. However, most MSMEs still face challenges such as low levels of digitalization, limited resources, and vulnerability to external shocks like pandemics. In this context, the Resource-Based View (RBV) emphasizes the importance of managing resources that are valuable, rare, inimitable, and non-substitutable (VRIN) as the foundation for competitive advantage. Meanwhile, Dynamic Capabilities (DC) are required to enable organizations to perform sensing, seizing, and reconfiguring in response to environmental opportunities and threats, while Entrepreneurial Orientation (EO)—including innovativeness, proactiveness, and risk-taking—encourages creativity and business growth. This study aims to analyze the influence of RBV, DC, and EO on MSME performance and Sustainable Competitive Advantage (SCA) in Bali Province. The research applies a quantitative approach with an explanatory design, involving 200 active MSME respondents who meet the operational criteria. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results show that all three variables—RBV, DC, and EO—have positive and significant effects on MSME performance and SCA. DC emerged as the most dominant factor in creating sustainable competitive advantage, followed by RBV and EO. These findings highlight that the integration of internal resource management, adaptive capabilities, and entrepreneurial orientation is a key strategy for Balinese MSMEs to sustain and excel in the digital transformation era.